2017
DOI: 10.2147/nrr.s131454
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge regarding postexposure prophylaxis of HIV among nurses

Abstract: Fifty nurses working in BP Koirala Memorial Cancer Hospital, Bharatpur, were selected by probability simple random sampling technique for determining the knowledge level about postexposure prophylaxis (PEP) of HIV among nurses during 2014. A descriptive design, semistructured self-administered questionnaire was used for the study. The study showed that 48% of respondents had knowledge on the meaning of PEP, only 39.39% respondents were aware of the first aid management getting needle prick injury, 60% were awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…Transmission via mucous membranes as well as through abraded skin is the least common mode of occupational HIV transmission. The average risk of percutaneous exposure following HIV exposure is estimated to be 0.3% and 0.09% after exposure to mucous membranes [8]. The studies showed that occupational exposures occur predominantly in developing countries, although they are infrequently reported [9,10].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Transmission via mucous membranes as well as through abraded skin is the least common mode of occupational HIV transmission. The average risk of percutaneous exposure following HIV exposure is estimated to be 0.3% and 0.09% after exposure to mucous membranes [8]. The studies showed that occupational exposures occur predominantly in developing countries, although they are infrequently reported [9,10].…”
Section: Resultsmentioning
confidence: 99%
“…The studies included in this paper revealed that nurses had inadequate knowledge regarding PEP [2,4,6,8,[24][25][26]. Despite varied level of knowledge nurses have regarding PEP, PEP remains the only ARV treatment regimen intended to reduce the occupational transmission of HIV [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations